Estimated values: the provisions and the write-downs of assets as tools to manipulate financial results of enterprises - Stępień, Konrad (Copernican Journal of Finance & Accounting, 2015)
The purpose of using estimated values such as: provisions and write-downs of assets is to limit economic risk. Provisions should protect the entity against the adverse effects of future economic events that are possible to predict, and the write-downs of assets should protect the entity against overvaluation of its assets beyond their true value. However, in business practice, these estimates, are often used by the boards of companies to manipulate financial results, both as a tool to increase, as well as to decrease the result. The purpose of this study is to point out the problem of manipulating financial results of companies through the use of estimated values in the form of provisions and write-downs of assets. It seems that it should be taken seriously, and considered as one of the key problems of the theory, and in particular the practice of accounting. The following research methods have been used: an analysis of the literature, an analysis of normative acts, deduction method and comparison method.